PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN PADA UMKM RESTU JAMUR LEBAK DI KP. BOJONG ASEM DESA RANGKASBITUNG BARAT KEC. RANGKASBITUNG - Yogi Teguh Saputro; Nurlaelah; Pindonta Nalsal Purba; Edi Sutanto; Ela Widasari (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2020)
In running a business, whether it is a large or small scale business, business actors are required to have good financial arrangements, such as in terms of financial management. A business can be said to be good if it has good financial management. In running its business, Blessing Mushroom Lebak still records simple financial reports in the form of income and expenses only, and a lack of knowledge about how to make financial reports is one of the reasons this business only carries out simple financial management. In this mentoring activity, the author carried out mentoring activities for Restu Mushroom Lebak MSMEs. with 4 members, the author tries to provide assistance or provide guidance to business actors, each member has their own responsibilities and duties in carrying out mentoring activities. The aim of this activity is to provide assistance on how to make financial reports in a good and structured manner in the form of recording transactions, making journals, posting them to the ledger, preparing profit and loss reports, preparing capital change reports, preparing balance sheets and cash flow reports. The conclusion from this mentoring activity is that the author hopes that business actors, in this case the blessing of Lebak Mushrooms, can make financial reports well and structured in accordance with existing standards.